Judgment Confidence and Judgment Accuracy of Teachers in Judging Self-Concepts of Students - Praetorius, Anna-Katharina; Berner, Valérie-Danielle; Zeinz, Horst; Scheunpflug, Annette; Dresel, Markus (The Journal of educational research (Washington, D.C.), 2013)
Accurate teacher judgments of student characteristics are considered to be important prerequisites for adaptive instruction. A theoretically important condition for putting these judgments into operation is judgment confidence. Using a German sample of 96 teachers and 1,388 students, the authors examined how confident teachers are in their judgments of students' mathematic and verbal self-concepts, and whether judgment confidence is related to judgment accuracy. Judgment confidence was largely student specific, and the majority of teachers were overconfident of their judgments. Moreover, teacher confidence was higher for extreme judgments. In the subject of mathematics, judgment confidence was moderately associated with judgment accuracy. The findings challenge the efficacy of adapting instruction to student characteristics, as it is obvious that many teachers are not aware of their judgment inaccuracy.